2016
DOI: 10.1080/15384101.2016.1241914
|View full text |Cite
|
Sign up to set email alerts
|

Histone chaperone ASF1B promotes humanβ-cell proliferation via recruitment of histone H3.3

Abstract: Anti-silencing function 1 (ASF1) is a histone H3-H4 chaperone involved in DNA replication and repair, and transcriptional regulation. Here, we identify ASF1B, the mammalian paralog to ASF1, as a proliferationinducing histone chaperone in human b-cells. Overexpression of ASF1B led to distinct transcriptional signatures consistent with increased cellular proliferation and reduced cellular death. Using multiple methods of monitoring proliferation and mitotic progression, we show that overexpression of ASF1B is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 74 publications
0
40
0
Order By: Relevance
“…ASF1 exists as two paralogs: ASF1A and ASF1B. ASF1A contributes primarily to DNA repair and cell senescence, while ASF1B is preferentially involved in cell proliferation 22,23 . Interestingly, Armelle et al revealed that a high mRNA level of ASF1B was correlated with clinical data and disease outcome in breast cancer, and the researchers proposed that ASF1B might be used as a new proliferation marker for breast cancer diagnosis and prognosis 24 .…”
Section: Introductionmentioning
confidence: 99%
“…ASF1 exists as two paralogs: ASF1A and ASF1B. ASF1A contributes primarily to DNA repair and cell senescence, while ASF1B is preferentially involved in cell proliferation 22,23 . Interestingly, Armelle et al revealed that a high mRNA level of ASF1B was correlated with clinical data and disease outcome in breast cancer, and the researchers proposed that ASF1B might be used as a new proliferation marker for breast cancer diagnosis and prognosis 24 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that depletion of histone H3–H4 chaperone Asf1b severely compromises proliferation, leading to aberrant nuclear structures and a distinct transcriptional signature, while its overexpression increases cellular proliferation, promoting tumor progression and predicting poor outcomes [ 25 ]. This effect of Asf1b was also observed in β cell proliferation [ 26 ]. Anln is an actin-binding protein required for cytokinesis.…”
Section: Discussionmentioning
confidence: 60%
“…In recent years, it has become increasingly clear that the different subunits of the ribonuclease P complex are engaged in other important roles. Pop4 has recently been shown to be involved in the DNA damage response machinery (Abu-Zhayia et al 2017), and to participate in the regulation of chromatin structure and function (Newhart et al 2016), which is known to play a fundamental role in the epigenetic modification of the genome and likely also in b-cell biology (Paul et al 2016). In humans, copy number variants of POP4 have been associated with breast and ovarian cancer (Wrzeszczynski et al 2011;Natrajan et al 2012).…”
Section: Discussionmentioning
confidence: 99%